2014
DOI: 10.1016/j.molonc.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase 1A3 influences breast cancer progression via differential retinoic acid signaling

Abstract: Aldehyde dehydrogenase (ALDH) 1A enzymes produce retinoic acid (RA), a transcription induction molecule. To investigate if ALDH1A1 or ALDH1A3-mediated RA signaling has an active role in breast cancer tumorigenesis, we performed gene expression and tumor xenograft studies. Analysis of breast patient tumors revealed that high levels of ALDH1A3 correlated with expression of RA-inducible genes with retinoic acid response elements (RAREs), poorer patient survival and triple-negative breast cancers. This suggests a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
174
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(194 citation statements)
references
References 56 publications
15
174
0
Order By: Relevance
“…In addition, they also found that ALDH1B1 is dramatically upregulated in human colonic adenocarcinoma and therefore considering it as a potential biomarker for human colon cancer (23). Although high ALDH1A3 levels have already been detected in more aggressive forms of breast, bladder, and lung cancers (18,22,26), this work is nevertheless the first, to our knowledge, to report that ALDH1A3 is the main ALDH isoenzyme in intrahepatic cholangiocarcinoma. More importantly, we also found that ALDH1A3 is a critical prognostic factor in 77 patients with intrahepatic cholangiocarcinoma who received hepatectomies among several clinicopathologic features.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, they also found that ALDH1B1 is dramatically upregulated in human colonic adenocarcinoma and therefore considering it as a potential biomarker for human colon cancer (23). Although high ALDH1A3 levels have already been detected in more aggressive forms of breast, bladder, and lung cancers (18,22,26), this work is nevertheless the first, to our knowledge, to report that ALDH1A3 is the main ALDH isoenzyme in intrahepatic cholangiocarcinoma. More importantly, we also found that ALDH1A3 is a critical prognostic factor in 77 patients with intrahepatic cholangiocarcinoma who received hepatectomies among several clinicopathologic features.…”
Section: Discussionmentioning
confidence: 57%
“…Elevated ALDH activity is also observed in leukemic SC populations in some acute myelogenous leukemia patients (13). ALDH1 serves as a marker of cancer SCs (CSC) in several types of solid tumors, including those of the liver (14), head and neck (15), pancreas (16), lung (17,18), prostate (19), bladder (20), ovary (21), breast (22), and colon (23). On the other hand, the potential of using increased ALDH activities to identify SC subpopulations in cholangiocarcinoma remains to be verified (24).…”
Section: Introductionmentioning
confidence: 99%
“…Cells with a CSC phenotype characterized by ALDH activity were shown to have an improved ability for metastatic behavior in vitro (adhesion, colony formation, migration, and invasion) and metastases in vivo, supporting the hypothesis that CSCs might act as metastasis-initiating cells (14,49,(52)(53)(54).…”
Section: Aldh1mentioning
confidence: 61%
“…Furthermore, increased expression of homeobox A1 and mucin 4 were associated with high ALDH1 activity, also contributing to tumor relapse and metastasis. Activation of transforming grow factor-beta 2 signaling pathway was also shown to be involved in the pathological regulation of ALDH1 in breast cancer (49)(50)(51).…”
Section: Aldh1mentioning
confidence: 99%
“…RNA isolation from frozen human breast tumour samples, gene microarray analysis and data processing were as described previously. 39 The mRNA levels were estimated based on normalized gene microarray signal intensity. The cutoff values to define 'high' and 'low' levels for each gene were determined with receiver operating characteristic (ROC) curve analysis.…”
Section: Methodsmentioning
confidence: 99%